A TEORI BILANGAN SEBAGAI SARANA PENGEMBANGAN BERPIKIR DEDUKTIF MAHASISWA DALAM PEMBELAJARAN MATEMATIKA - Rika Septianingsih; Tasya Indri Rangkuti; Meliya Afprida (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasir Pengaraian, 2025)
This study aims to describe the initial mathematical ability of students in a Mathematics Education program in the context of developing deductive thinking through number theory learning. The research employed a descriptive quantitative approach with 17 students as participants. Data were collected through a deductive thinking ability test and analyzed using descriptive statistics by categorizing students’ abilities into low, medium, and high levels. The results indicate that the average level of students’ deductive thinking ability falls within the medium category, with considerable variation among students. These findings suggest that differences in initial mathematical ability influence students’ deductive reasoning processes in understanding concepts, formalizing arguments, and solving number theory problems. Therefore, mapping students’ initial mathematical ability is an important step in designing adaptive learning strategies that support the strengthening of deductive thinking in higher education.